Effect of insert micro-texture types on the cutting force and temperature under various cooling conditions. (24th February 2022) - Dai, Longjie; Zheng, Jintao; Dong, Delong; Sun, Shufeng; Liu, Guoliang
Micro-texturing has been widely recognised an effective method for achieving sustainable metal cutting. However, the micro-textures were mainly studied under dry cutting condition, and the cutting performance of micro-textured inserts under different cooling conditions has not been widely reported. In this paper, the untextured, linear micro-grooved, and curvilinear micro-grooved inserts were used to cutting aluminium alloy 6061 under dry, emulsion, and liquid nitrogen cryogenic cooling conditions, and the cutting force and temperature were studied. The results indicated that the microgrooves on insert surface can obviously reduce the cutting force and temperature under all cooling conditions, and the benefit of curvilinear micro-grooves was more significant. The benefit of linear micro-grooves on reducing cutting force under emulsion and cryogenic cooling conditions was weaker than that under dry cutting condition, because of the derivative cutting phenomenon. The combination of curvilinear micro-grooves and cryogenic cooling condition can generate positive effect on reducing cutting force and temperature.